Unraveling the Versatility of Carbon Black - Polylactic Acid (CB/PLA) 3D-Printed Electrodes via Sustainable Electrochemical Activation - Papavasileiou, Anastasios V; Děkanovský, Lukáš; Chacko, Levna; Wu, Bing; Luxa, Jan; Regner, Jakub; Paštika, Jan; Koňáková, Dana; Sofer, Zdeněk (Small methods, 2025)
Commercially available conductive filaments are not designed for electrochemical applications, resulting in 3D printed electrodes with poor electrochemical behavior, restricting their implementation in energy and sensing technologies. The proper selection of an activation method can unlock their use in advanced applications. In this work, rectangular electrodes made from carbon black - polylactic acid (CB/PLA) filament are 3D printed with different layouts (grid and compact) and then activated using a highly reproducible eco-compatible electrochemical (EC) treatment. The electrodes are characterized for their morphological, structural, and electrochemical features to obtain insights into the material properties and functionality. Furthermore, the influence of the electrode layout as well as the activation conditions are studied aiming to provide a better understanding of the mechanism driving the electrochemical behavior of the electrodes. The EC activation enhances the electrochemical performance, provides a uniform electrochemical activity in the electrode's interface and allows the manipulation of the electrochemical properties of 3D printed electrodes by adjusting the duration of the treatment. CB/PLA electrodes offer a wide stable potential window that benefits their use in water-based electrochemical applications. Thus, their suitability for Zn-ion batteries and electrochemical sensing is explored, followed by their application in hydroquinone determination in water samples.
Keywords: sensing; grid‐layout electrode; aqueous battery; electrochemical activation; 3D printed electrodes